FORMULATION AND IN VITRO, IN VIVO EVALUATION OF PRONIOSOMAL GEL OF NEOMYCIN SULPHATE - SHETE, AMOL; THORAT, PRIYANKA; DOIJAD, RAJENDRA; SAJANE, SACHIN (International Journal of Applied Pharmaceutics, 2019)
Objective: The objectives of present investigation were to prepare and evaluate proniosomes of neomycin sulphate (NS) by coacervation phase separation method by using sorbitan monostearate (span 60) and lecithin as a surfactant to increase the penetration through the skin and study the effect of concentration of the same. Methods: Proniosomes of neomycin sulphate (NS) were prepared by coacervation phase separation method by using span 60 and lecithin. The effect of concentration of span 60 and lecithin was studied by factorial design. The prepared proniosomes were converted to gel by using carbopol as a gelling agent. The prepared formulations were evaluated for entrapment efficiency, in vitro drug diffusion, in vitro antibacterial activity and in vivo skin irritation test etc. Results: All Formulation showed the percentage entrapment efficiency in the range 38.31±0.05% to 77.96±0.06%, good homogeneity and gel was easily spreadable with minimal of shear. Optimized formulation showed enhanced rate of diffusion in vitro, increase in zone of inhibition against staphylococcus aureus, no skin irritation and showed good stability. Conclusion: The results of present study indicates that proniosomal gel formulated by using combination of span 60, Lecithin, cholesterol can be used to enhance skin delivery of NS because of excellent permeation of drug. Developed proniosomal gel formulation was promising carrier for NS